Peningkatan Mutu Pembelajaran di SMK Pariwisata Bantul melalui Pelatihan Marbling Technique - Wahyu Eka Priana Sukmawaty; Damayanti, Sri (Yayasan Literasi Sains Indonesia, 2025)
This marbling technique training aims to improve the quality of learning at the Bantul Tourism Vocational School. The quality of learning is a crucial factor in achieving optimal graduate competence. The activity was carried out on November 7, 2024, at the sewing practice room of the Bantul Tourism Vocational School. This activity took place from 10.00-13.00 WIB. The methods used include theoretical sessions related to the introduction of the meaning of marbling, equipment for marbling with acrylic paint and steps for marbling (fabric mordanting process, making water media, preparing and checking paint, motif making process, rinsing process, drying process and fixation process). The output of this activity is that students and teachers gain new knowledge related to marbling techniques. Teachers can integrate these techniques into recommended learning, namely cultural arts, creative product design, crafts, fabric decoration, and entrepreneurship as well as establish partnerships with art raw material distributors or develop local raw materials. Additional training is needed to improve the final quality of the product to match the tourism market standards. It is hoped that integration can enhance the quality of learning at SMK Pariwisata Bantul.